Kino przestronnego kadru - Pławuszewski, Piotr (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2011)
Cinema of a large frame The first edition of American Film Festival took place in Wrocław (20-24/11/2010) and became a great opportunity to watch both the classic and the latest movies made by the American filmmakers. The article Kino przestronnego kadru (Cinema of a large frame) focuses on the festival documentary section. From among the titles that are mentioned, a special author’s attention is dedicated to two movies: And Everything Is Going Fine (directed by Steven Soderbergh, 2010; a haunting picture of life and death of Spalding Gray, American writer and performer of self-written monologues) and Two Escobars (directed by Jeff and Michael Zimbalist, 2010; a story about the Colombian mafia, soccer, drugs, heroes, bandits and much more). Despite many differences beetwen them, each represents a fine art of making remarkable and moving documentaries and for sure it’s worth interest.